2020
DOI: 10.1038/s41598-020-76346-1
|View full text |Cite
|
Sign up to set email alerts
|

Insights in the regulation of trimetylamine N-oxide production using a comparative biomimetic approach suggest a metabolic switch in hibernating bears

Abstract: Experimental studies suggest involvement of trimethylamine N-oxide (TMAO) in the aetiology of cardiometabolic diseases and chronic kidney disease (CKD), in part via metabolism of ingested food. Using a comparative biomimetic approach, we have investigated circulating levels of the gut metabolites betaine, choline, and TMAO in human CKD, across animal species as well as during hibernation in two animal species. Betaine, choline, and TMAO levels were associated with renal function in humans and differed signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 101 publications
0
19
0
Order By: Relevance
“…Hibernators have been described to have developed natural resistance to chronic kidney disease (CKD), often associated with cardiovascular impairments in humans (for reviews, see Romagnani et al, 2017 ; Sarnak et al, 2019 ), despite their long hibernation fast during winter. Indeed, it was recently reported that markers of CKD differed significantly between animal species with different feeding habits and thermoregulatory behaviors, and that hibernating brown bears and garden dormice displayed higher levels of betaine and choline (known to be cardioprotective) and lower, sometimes even non-detectable, levels of trimethylamine N-oxide (TMAO), a marker of CDK in human and animals ( Ebert et al, 2020 ). Hence, the betaine endogenously produced by the organism may protect organs (notably kidney) of bears, dormice, and other hibernators from oxidative or other damages during the hibernation period of depressed metabolism.…”
Section: Protective Mechanisms During the State Of Metabolic Depressimentioning
confidence: 99%
“…Hibernators have been described to have developed natural resistance to chronic kidney disease (CKD), often associated with cardiovascular impairments in humans (for reviews, see Romagnani et al, 2017 ; Sarnak et al, 2019 ), despite their long hibernation fast during winter. Indeed, it was recently reported that markers of CKD differed significantly between animal species with different feeding habits and thermoregulatory behaviors, and that hibernating brown bears and garden dormice displayed higher levels of betaine and choline (known to be cardioprotective) and lower, sometimes even non-detectable, levels of trimethylamine N-oxide (TMAO), a marker of CDK in human and animals ( Ebert et al, 2020 ). Hence, the betaine endogenously produced by the organism may protect organs (notably kidney) of bears, dormice, and other hibernators from oxidative or other damages during the hibernation period of depressed metabolism.…”
Section: Protective Mechanisms During the State Of Metabolic Depressimentioning
confidence: 99%
“…Other cardiac adaptions during hibernation, such as decreased functional measures of myocardial velocities 39 may also be operative. Finally, a metabolic switch that shunts choline to generate betaine instead of the pro-atherogenic toxin Trimetylamine N-oxide (TMAO) during hibernation could hold clues for novel treatment options in burden of lifestyle diseases 40 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular betaine levels, a primary source of methyl donors, is derived via the same biochemical pathway as TMAO, albeit on a different branch. It is therefore of note, that we recently reported that free-ranging brown bears may turn on a metabolic switch that in hibernation shunts choline to generate betaine instead of TMAO [61], thus decreasing inflammatory burden and enabling epigenetic changes in preparation for the metabolic changes occurring on emergence from hibernation. Characterisation and better understanding of such an adaptive switch turning on and off TMAO generation could hold clues for novel treatment options in burden of lifestyle diseases.…”
Section: Figure 1 Dietary Intake Tmao Metabolism and Disease Riskmentioning
confidence: 94%